Can the modeling for simplification of a dental implant surface affect the accuracy of 3D finite element analysis?. Issue 15 (17th November 2016) - Verri, Fellippo Ramos; Cruz, Ronaldo Silva; de Souza Batista, Victor Eduardo; Almeida, Daniel Augusto de Faria; Verri, Ana Caroline Gonçales; Lemos, Cleidiel Aparecido de Araújo; Santiago Júnior, Joel Ferreira; Pellizzer, Eduardo Piza
Abstract: The aim of this study was to assess stress/strain of different implant modeling simplifications by 3D-FEA. Three variation of external hexagon implant (Ø3.75 × 10 mm) supporting one molar crown were simulated: A (no threads); B (slightly threads simplification); C (original design). 200 N (axial) and 100 N (oblique) were applied. Cortical bone was evaluated by maximum principal stress and microstrain qualitatively and quantitatively (ANOVA and Tukey post hoc ( p  < 0.05)). Higher stress levels ( p  < 0.05) were observed in model A. Models B and C presented similar stress transmission. It was possible to conclude that slightly simplification should be used for studies evaluating stress transferring for bone tissue.